Evaluasi Kebijakan Pemberian Insentif Pajak Bagi Wajib Pajak yang Terdampak Covid-19: Studi Kasus di KPP Wajib Pajak Besar Satu - Heri Hendrianto; Hasan Rachmany (Jurnal Pajak Vokasi (JUPASI), 2026)
The Covid-19 pandemic has caused a major shock to the national economy, prompting the government to issue tax incentive policies to ease the burden on taxpayers. This study evaluated the tax incentive policy for taxpayers affected by covid-19 at the Large Tax Office One (KPP Wajib Pajak Besar Satu) using the six public evaluation criteria by William Dunn: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The research adopts a qualitative approach, with data collected through in-dept interviews and document analysis. The problem formulation includes questions regarding the background of the tax incentive regulation implementation, obstacles that hinder optimal execution, and proposed actions to prevent the recurrence of similar phenomena. The objectives of the study include understanding the policy background, identifying the causes of suboptimal implementation, and formulating appropriate recommendations. The results show that the implementation of the tax incentive policy was relatively effective and efficient, although there were administrative barriers, limitations related to business field classification (KLU), and a lack of public outreach. This study recommends simplifying procedures and expanding the scope of incentives in the future as part of an emergency fiscal response. Keywords: Policy Evaluation; Tax Incentives; Covid-19; Taxpayer; Large Tax Office